The "Roll Yield" Myth. Issue 2 (1st April 2018) - Bessembinder, Hendrik
Abstract : Futures investors are frequently said to periodically pay or receive the difference in futures prices across contracts with different delivery dates. But this "roll yield" is mythical: No such cash flow occurs—at the time of roll trades or on any other date. However, although the term is a misnomer, the roll yield does contain useful information. It explains when futures gains exceed or fall short of spot-price changes, and for storable assets, it provides information regarding benefits to the marginal holder of a spot position. This article clarifies the actual role of the roll yield. Abstract : Disclosure: The author reports no conflicts of interest. Editor's Note This article was externally reviewed using our double-blind peer-review process. When the article was accepted for publication, the author thanked the reviewers in the acknowledgments. Hilary Till was one of the reviewers for this article. Submitted 21 September 2017 Accepted 6 February 2018 by Stephen J. Brown